Prenatal Diagnosis and Successful Outcome in Neonate of Aorto‐Left Ventricle Tunnel. Issue 1 (16th October 2013) - Jone, Pei‐Ni; Mitchell, Max B.; Campbell, David N.; da, Eduardo M.
<x xml:space="preserve">Abstract</x> Aorto‐left ventricular tunnel (ALVT) is an abnormal congenital communication between the ascending aorta and the left ventricle. Prenatal diagnosis is rare and can be misinterpreted as aortic insufficiency on fetal echocardiogram. We present a case of ALVT diagnosed in a fetus who underwent successful early neonatal surgical repair.